The Explanation of Suicide Ideation: Application of General Strain Theory - akbar aliverdinia; neda yousefi (توسعه اجتماعی)
Today, suicide is the most serious and the most dangerous social damage that we are witnessing a growing trend among teenagers and young adults. With increase rate this injury among young people society Necessity serious research and strategies to prevent it seriously will feel. The main objective of this study is a sociological explanation suicide ideation among students of Mazandaran University. Research method is survey and cross-sectional. The population consists of all girl and boy students (9940) Mazandaran University who were studying in school (academic) year of 2012-2013. A total of 438 subjects selected by random stratified sampling proportional. Research findings suggest that there were significant differences between girls and boys in ideation suicide. Also, removal of positive stimulus, the presence of negative stimuli, negative emotional states and deviant behaviors to the dependent variable (suicide ideation) there are direct and significant relationship. Multiple regression analysis results also show that Negative emotional states variable (beta coefficient=0/479) and removal of positive stimulus (beta coefficient=0/079) respectively are the strongest and lowest predictors of suicide ideation.